Role of the protein annexin A1 on the efficacy of anti-TNF treatment in a murine model of acute colitis - de Paula-Silva, Marina; Barrios, Bibiana Elisabeth; Macció-Maretto, Lisa; Sena, Angela Aparecida [UNESP]; Farsky, Sandra Helena Poliselli; Correa, Silvia Graciela; Oliani, Sonia Maria [UNESP] (Elsevier, 2016)
TNF-α is involved in the mechanisms that initiate inflammatory bowel diseases (IBDs). Anti-TNF-α drugs, such as infliximab (IFX), cause non-responsiveness and side effects, indicating the need to investigate alternative therapies for these diseases. The anti-inflammatory protein, annexin A1 (AnxA1), has been associated with the protection of the gastrointestinal mucosa. To further address the role of endogenous AnxA1 on the TNF-α blockade efficacy in a murine model, we assessed colitis induced by Dextran Sulfate Sodium (DSS) in wild-type (WT) and AnxA1−/− Balb/c mice treated with IFX. We consistently observed endogenous AnxA1 prevented clinical and physiological manifestations of experimental colitis treated with IFX, additionally the manifestation of the disease was observed earlier in AnxA1−/− mice. Rectal bleeding, diarrhea, histological score, epithelial damages and collagen degradation caused by DSS were prevented following IFX treatment only in WT mice. IL-6 increased during colitis in WT and AnxA1−/− mice, decreasing under IFX treatment in WT. The influx of neutrophils and TNF-α secretion were largely elevated in AnxA1−/− mice when compared to WT mice. In the group WT/DSS + IFX, phagocytes were more susceptible to apoptosis following treatment with IFX. Endogenous expression of AnxA1 increased after DSS and decreased with IFX treatment, demonstrating an attenuated inflammatory response. The data indicate that AnxA1 contributes to the establishment of intestinal homeostasis after blocking of TNF-α was used as a treatment of IBD, constituting a key molecule in the mechanism of action and a potential biomarker of therapeutic efficacy.
Keywords: Annexin A1; Biomarker; Colitis; Infliximab; Therapy; TNF-α